Peran Guru Bimbingan dan Konseling dalam Membantu Siswa Sekolah Menengah Pertama Mengatasi Rasa Takut Bertanya di Kelas - Yuniati Sangga; Nofriyanti Lindayan; Jelsika Yohanis Sonda; Syukur Bantuk (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
The purpose of this research is to examine how guidance and counseling instructors may help children in junior high get over their anxiety about speaking out in class. Students' lack of confidence and engagement in class might be exacerbated by the widespread problem of their fear of asking questions. In order to delve further into the issue, this study used a descriptive technique based on qualitative research. Students and instructors of guidance and counseling participated in interviews and observations to compile the data. The results highlight the important role that counseling and guidance instructors play in assisting students in coping with anxiety. Counseling sessions with individuals, group guidance exercises, and making an attempt to establish a welcoming classroom setting all contribute to this goal. Teachers also use excellent communication tactics and motivating initiatives to help pupils feel more comfortable expressing themselves. A more favorable classroom environment may also be achieved via collaboration between topic teachers and counseling instructors. Ultimately, the research demonstrates that students' anxiety of asking questions may be successfully reduced via the use of suitable counseling and guiding interventions. Consequently, students' self-esteem, classroom engagement, and academic performance are all much improved when guidance and counseling instructors are present.